Inflation, unemployment and crime rate in Nigeria - Wilfred, Akinola Gbenga (Journal of Social Economics Research, 2025)
An acute inflationary economy exacerbates the conditions of the unemployed, potentially making criminal activities more appealing to those without employment. The nexus between unemployment, inflation, and crime rates in any given economy remains a subject of ongoing debate in the literature. Consequently, this article examined the effects of unemployment and inflation on the crime rate in Nigeria, guided by these research questions: (1) What is the trending nexus between inflation, unemployment, and crime rate in Nigeria? (2) What are the effects of unemployment and inflation on the crime rate in Nigeria? (3) What is the direction of causality between unemployment, inflation, and the crime rate in Nigeria? Descriptive statistics, ARDL, and the Toda-Yamamoto causality test were the study’s estimating techniques employed to address the research questions. Evidence from the study’s outcomes showed that unemployment and government spending on education negatively impact the crime rate both in the short and long run. Furthermore, the Toda-Yamamoto causality result demonstrated the existence of bidirectional causality between educational spending and the crime rate in Nigeria. It clearly indicates that crime rates Granger cause educational spending and vice versa. This implies that as government spending on education fails to reduce school dropout rates, it results in the proliferation of criminal activities. Conversely, the crime rate Granger causes educational spending as a measure to control criminal activities. It is recommended that government expenditure be directed towards appropriate sectors to create employment opportunities for the unemployed, thereby contributing to a decline in the crime rate in Nigeria.